Elaboración de una multimedia como herramienta en el proceso de enseñanza - aprendizaje en los estudiantes de bachillerato y básica superior con discapacidad intelectual de la unidad educativa especializada Gladys Flores Macías año 2017 – 2018. - Carrillo Llumitaxi, Edison Patricio (2017)
This project has been developed with the purpose of supporting and facilitating the teaching of students with intellectual disabilities, the application was developed with the requirements of the teachers of the Specialized Educational Unit "Gladys Flores Macias", to provide a study process functional to students with the aforementioned condition. The project aims to bring together students with disabilities and technology, so that learning is more interactive and dynamic, obtaining better results. The application was developed with the HAEduc author language program, which allows us to develop: Dynamic and interactive material easy to understand for students, Grouping of several multimedia files, Tool based on the requirements of the teachers of the Educational Unit "Gladys Flores Macías". Activities to interact in an efficient way The project ended when tested, manipulated and approved by the teachers together with the students, whose behavior and attitudes culminated with interest, joy and enthusiasm to continue participating.